EFFECT OF GEOPHYSICAL PARAMETERS ON ATTENUATION OF CONTAMINANT IN FRESHWATER COASTAL AQUIFERS - ADEGOKE JAMES ADEYEMO; OLATUNDE I. POPOOLA; OLUDOTUN OMONIYI FALUYI (Journal of Engineering Studies and Research)
Freshwater coastal aquifers can be contaminated by influx of seawater. The study investigated the effect of geophysical parameter such as seepage velocity (v) determined empirically on the mass flux (J) of contaminant through the coastal aquifers. Porosities of the grains were determined and tagged samples A to E. v was obtained in the experimental setup. Results showed that hydraulic gradient ranged between 3.233 to 0.317 while the corresponding values of contaminant J ranged between 0.302 to 5.381 Kgm-2s-1 within 60 to 360 seconds. Therefore, the attenuation coefficients of J decreased with increased in flow rate of fluid through the samples.